2018
DOI: 10.5530/pj.2018.4.106
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Terpenoids from Thuidium tamariscellum (C. Muell.) Bosch. and Sande-Lac. a Moss

Abstract: Introduction:Thuidium tamariscellum is a small creeping epiphytic moss growing on trunks and branches of trees as well as on moist shady rocky surface at high altitudes areas. Methods: The present study was undertaken to analyze the phytochemicals in the species and its antioxidant potentialities interms of DPPH, ABTS, H 2 O 2 , FRAP and metal chelating ability. Results: Total terpenoids level was remarkable. Interestingly, a concentration dependent free radical scavenging potential was noticed and was compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
0
16
0
6
Order By: Relevance
“…The phytochemical studies on Thuidium tamariscellum showed the presence of significant level of terpenoids in the moss. High antioxidant property shown by the plant is reported to be mainly due to the presence of considerable amount of terpenoids [38].…”
Section: Antioxidant Property In Bryophytesmentioning
confidence: 99%
“…The phytochemical studies on Thuidium tamariscellum showed the presence of significant level of terpenoids in the moss. High antioxidant property shown by the plant is reported to be mainly due to the presence of considerable amount of terpenoids [38].…”
Section: Antioxidant Property In Bryophytesmentioning
confidence: 99%
“…The antioxidant properties of S. coronopifolius extract may be related to their chemical composition, such as the content of phenolic compounds or other substances isolated like bromoditerpenes and sulfated polysaccharides 11,12 . Some studies have shown that terpene compounds are responsible for a strong antioxidant activity 44,45,46 . Furthermore, de Menezesda Silveira et al, 33 found that a sample of Brazilian yellow propolis, which is rich in triterpenes showed antidepressantlike activities.…”
Section: Animal Body and Organ Weightsmentioning
confidence: 99%
“…Terpenoids as antioxidants mop-up free radicals, react with peroxyl radicals, thereby terminating oxidative chain reactions. 19 Comparing the antioxidant activities of the n-butanol sub-fractions with the chemical class of compounds dereplicated (Figure 1 Figure 2).…”
Section: Hplc-ms Analysismentioning
confidence: 99%
“…The base peak chromatograms of the active sub-fractions and the compound spectra of the constituents tentatively characterized are presented in Figures S1 and S2 respectively. Many important potential active compounds such as pimpinellin (1), quercitrin (2), piperlonguminine (3), matairesinol (4), datiscin (5), savinin(26), stigmasterol (8), β-sitosterol (9), zanthosinamide (11), myricetin(12), eriocitrin (13), diosmin(14), magnoflorine (15), berberine(16), sesamin (hinokinin)(17), campesterol (10), kaempferol(18), dioxamin(19), rutin (30), marmesin (20), fagaramide (6), oxychelerythrine(28), scoparone(27), quercetin (7), arnottianamide(29), skimmianine(25), herclavine(24), lemairamin(23), fagaronine(22) and lupeol(21) have been tentatively characterized from Z. zanthoxyloides leaves. In this study, many phytochemicals such as coumarins (3), flavonoids(8), alkaloids(12), lignans (3) and triterpenes (4) were found in different VLC fractions of n-butanol soluble fraction of Z. zanthoxyloides leaves…”
mentioning
confidence: 99%